Nikon D3000 digital field guide - Thomas, J. Dennis (Digital field guides., 2010)
"What do you need to take amazing photographs with your new Nikon D3000? This Nikon D3000 Digital Field Guide has all the answers. This full-color guide, perfectly sized to fit in your camera bag, not only explains all essential controls, features, and functions, it also goes well beyond the basics to give you a photography refresher on lighting, composition, exposure, and more. You'll find step-by-step, easy-to-follow instructions and full-color images of menu screens. Even better, it also offers tips and tricks to help you take your best shots, whether you're shooting portraits, candid shots, sports or travel photos, or macro photography"--Resource description page.